2021
DOI: 10.1007/s11136-020-02740-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological risk factors that characterize the trajectories of quality of life after a physical trauma: a longitudinal study using latent class analysis

Abstract: Background The course and corresponding characteristics of quality of life (QOL) domains in trauma population are unclear. Our aim was to identify longitudinal QOL trajectories and determine and predict the sociodemographic, clinical, and psychological characteristics of trajectory membership in physical trauma patients using a biopsychosocial approach. Methods Patients completed a questionnaire set after inclusion, and at 3, 6, 9, and 12 months follow-up.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The extent of recovery among motorcyclists at 12-months post-injury, was significantly greater among those whose baseline mental health was better (lower baseline DASS and PCS), who reported less pain post-crash and who had shorter length of stay (implying lower injury severity). Visser et al [ 41 ] recently reported similar findings in a land transport crash cohort, where higher baseline scores for anxiety and depressive symptoms were predictive of poorer outcomes at 12 months post-crash. While Visser’s cohort included all road user types, they evaluated them as one group only, their conclusions, supported by our study findings, suggests that early screening could identify those at risk of poorer psychological outcomes.…”
Section: Discussionmentioning
confidence: 67%
“…The extent of recovery among motorcyclists at 12-months post-injury, was significantly greater among those whose baseline mental health was better (lower baseline DASS and PCS), who reported less pain post-crash and who had shorter length of stay (implying lower injury severity). Visser et al [ 41 ] recently reported similar findings in a land transport crash cohort, where higher baseline scores for anxiety and depressive symptoms were predictive of poorer outcomes at 12 months post-crash. While Visser’s cohort included all road user types, they evaluated them as one group only, their conclusions, supported by our study findings, suggests that early screening could identify those at risk of poorer psychological outcomes.…”
Section: Discussionmentioning
confidence: 67%
“…Visser et al [26] proposed a new psychological trajectory identification process using the latent class analysis process.…”
mentioning
confidence: 99%
“…Injuries like amputations, multiple long bone fractures, or complex panfacial fractures result in an ISS < 15, but can heavily impact daily life and recovery trajectories. Third, patients at risk for impaired health status can be identified by symptoms of anxiety or depression, acute stress disorder, post-traumatic stress disorder, neuroticism, and trait anxiety, and in general not on sociodemographics or clinical outcome measures [43] . Fourth, level I trauma centres might not have reached their optimal volume of major trauma patients for an ideal exposure/skills and ownership/coordination ratio [44] .…”
Section: Discussionmentioning
confidence: 99%